All autonomy is not created equal: the countervailing effects of salesperson autonomy on burnout. Issue 3 (3rd July 2018) - Matthews, Lucy; Beeler, Lisa; Zablah, Alex R.; Hair, Joe F.
Abstract : Autonomy is commonly regarded as a desirable element of an employee's psychological climate that has the potential to reduce salesperson burnout. The literature is silent, however, regarding whether these beneficial effects of autonomy materialize when salespeople are tasked with making decisions that are likely to have adverse effects on the customers they serve. Building on work stress theories and data provided by a sample of 235 business-to-business (B2B) salespeople, this study posits and finds that salesperson customer relationship management (CRM) autonomy can increase or decrease salesperson burnout, depending on the nature of the CRM task at hand and prevailing conditions. To illustrate, the findings reveal that – depending on moderating factors – autonomy to create value can have a desirable or no effect on salesperson emotional exhaustion, personal accomplishment, and customer depersonalization. By contrast, the findings also reveal that autonomy to appropriate value increases emotional exhaustion among inexperienced salespeople, has mixed effects on personal accomplishment (depending on the selling time available to the salesperson), and increases customer depersonalization among salespeople who lack a customer orientation. This study underscores that, contrary to common wisdom, increasing salesperson autonomy is not a universally effective prescription for reducing salesperson burnout and its undesirable consequences.